Distribution, Severity, and Root Causes of Traffic Accidents in a Logistics Company - Syifa Ula Hamidya; Muhammad Addin Rizaldi; Suratman Suratman; Khaidar Ali; Nur Ulfah (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Traffic accidents are the main issue in logistics and transportation, causing health and economic losses, including lowering productivity. The study aimed: 1) to investigate the distribution of accidents, 2) to examine the category and severity of accidents based on operational type, and 3) to evaluate the root cause of accidents in logistics/goods transportation. This quantitative study was conducted in Indonesia using the data from Logistics Corporation from 2022 to 2023. The variable consists of operational type, accident category, severity, and root cause. This study was analysed using descriptive and inferential statistics. The chi-square was used to examine the statistical test, with the alpha set at 5%. The analysis was performed in Stata Ver 13 (College Station, TX, USA). A total of 288 accidents were reported during 2022-2023, with the accidents being highly distributed on Java (50%) and Sumatra (44.79%). The Accident category noted that collisions with objects, hits, and single-vehicle accidents are prevalent. The accident severity is as follows: minor severity (83.33%) and higher minor severity (16.67%). The statistical test also exhibits a significant on accident severity between last mile and long haul (p value < 0.05). According to operational type, long-haul operations have high accident intensity, while last-mile operations have severe accidents. The root cause of the accident is caused by third-party error (32.98%), followed by driver behavior (30.56%), driver competence (13.88%), and driver distraction (6.59%). The company should establish regulations, standard operating procedures (SOPs), work shift schedules, and vehicle maintenance protocols, and ensure their implementation. Additionally, measuring stress levels and work-related fatigue among drivers should be conducted to help prevent accidents.